Prevalence and Role of Risk Factors for Hypertension in 18-70 Years of Age in Rural and Urban Areas of District Sahiwal, Punjab Pakistan: Hypertension in 18-70 years of age in rural and urban areas of District Sahiwal - Anees Ur Rehman, Muhammad; Ashfaq, Khuram; Sohail, Nayab; Ghaffari, M. Abuzar; Ali, Nasir (Pakistan Journal of Health Sciences, 2022)
Globally, cardiovascular illnesses are believed to have hypertension as their primary cause and most important contributing factor. According to Pakistan’s National Health Survey, 33% of adults over the age of 45 and 18% of adults generally have hypertension. Objective: To determine the prevalence of hypertension and its risk factors in both urban and rural District Sahiwal, Punjab, Pakistan. Methods: The population under consideration includes people from both urban and rural regions of three hospitals for identification of hypertension. Questions regarding behavior including food, cigarette, and alcohol intake were posed. The behavioral calculations followed the physical measurements. After the patient had been at ease for 20 minutes, blood pressure was taken, and the person’s BMI. Results: With an increase in age, hypertension prevalence occurs suddenly. The frequency of hypertension was 4.27% in the age group of 20-29 years, rising to 59.72% up to the maximum frequency in the age group of 50-59 years, after which it significantly decreased to 56.79%. Out of 500 men, 162 (32.4%) and 170 (34%) of 500 females had hypertension. The percentage of hypertensive was 168 (33.6%) and 164 (32.8%) out of 500 respondents in rural and urban regions, respectively. Conclusions: In this study, the prevalence of hypertension suggests that it is becoming more prevalent. The key contributors to this emerging trend include urbanization, lifestyle modifications, and nutrient deficiencies